The Impact of Social Media on the Use of Code Mixing by Generation Z - Tarihoran, Nafan; Fachriyah, Eva; Tressyalina; Sumirat, Iin Ratna (International Journal of Interactive Mobile Technologies (iJIM), 2022)
Generally, generation Z mixes English and Indonesia when communicating with each other. This is a sociolinguistic phenomenon called code-mixing, which impacts social media as a part of the development of Information Communication Technology (ICT). Therefore, this study investigates the impact of social media on the use of code-mixing by generation Z. This study was carried out at Serang Raya University, Indonesia, where English is the only foreign language used to teach students. The research also aims to highlight the contribution of social media in code-mixing and determine the reasons this generation uses English and Indonesian in social media. Data were collected through self-completed questionnaires and interviews. The results showed that the use of social media had an impact on code-mixing between Indonesian and English for Gen Z.